2018
DOI: 10.1016/j.yebeh.2018.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Predicting drug-resistant epilepsy — A machine learning approach based on administrative claims data

Abstract: Objective: To determine whether information in medical and pharmacy claims data can predict, at the time of prescribing the first antiepileptic drug (AED), which patients with epilepsy will become resistant to AEDs. Method: We analyzed longitudinal claims data from 1,376,756 patients with epilepsy from 2006 to 2015. Of these, 582,258 satisfied all inclusion criteria; 49,916 were ultimately AED resistant, operationally defined as a patient with claims filed for at least 4 distinct AEDs. We constructed 1,270 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 53 publications
3
49
0
1
Order By: Relevance
“…Many machine learning models for mortality prediction in other domains include significantly more patients. Despite this, the model was able to achieve AUC 0.65, which is consistent with performance of models for similarly challenging healthcare-related prediction problems [9,26].…”
Section: Discussionsupporting
confidence: 67%
“…Many machine learning models for mortality prediction in other domains include significantly more patients. Despite this, the model was able to achieve AUC 0.65, which is consistent with performance of models for similarly challenging healthcare-related prediction problems [9,26].…”
Section: Discussionsupporting
confidence: 67%
“…More recently, An et al compared machine learning algorithms for prediction of drug‐resistant epilepsy (defined as requiring more than three medication changes during the study period) utilizing comprehensive U.S. claims data from 2006 to 2015. The authors found that the best‐performing algorithm, a random forest classifier trained using 635 features (comprising demographic variables, comorbidities, treatment regimens, insurance data, and clinical encounters) from 175 735 records, yielded an AUC of 76.4% and could identify patients with drug‐resistant epilepsy an average of 1.97 years before failing a second medication trial, using data available at the time of the first medication prescription …”
Section: Applications In Medical Management Of Epilepsymentioning
confidence: 99%
“…The authors found that the best-performing algorithm, a random forest classifier trained using 635 features (comprising demographic variables, comorbidities, treatment regimens, insurance data, and clinical encounters) from 175 735 records, yielded an AUC of 76.4% and could identify patients with drug-resistant epilepsy an average of 1.97 years before failing a second medication trial, using data available at the time of the first medication prescription. 88 A number of studies have also demonstrated the capabilities of machine learning algorithms in predicting individual medication responses. Devinsky et al examined clinical characteristics (eg, type and number of medications used, age, and comorbidities) from records of 34 990 patients extracted from a medical claims database, and trained a random forest classifier to predict a medication regimen least likely to require changes in the following 12 months (serving as a proxy of regimen efficacy and tolerability).…”
Section: Management Of Epilepsymentioning
confidence: 99%
“…Failure of ≥ 2 AEDs trials is a commonly faced problem in epilepsy practice which needs meticulous assessment of patients for proper management [17]. The current study showed nearly one-third of originally diagnosed DRE patients in the epilepsy clinic had NEEE due toimprecise initial diagnosis of functional seizures because of SSA and/or EEG misinterpretation as well as faulty diagnosis of frequent pseudo-seizures occurring in controlled epileptic patients relied on the previous organic epileptic nature of their illnesses.…”
Section: Discussionmentioning
confidence: 69%